1989
DOI: 10.1136/jnnp.52.6.736
|View full text |Cite
|
Sign up to set email alerts
|

Temporal lobe structure as determined by nuclear magnetic resonance in schizophrenia and bipolar affective disorder.

Abstract: SUMMARY Temporal lobe structure has been assessed by magnetic resonance imaging in groups of patients with schizophrenia (n = 21) bipolar affective disorder (n = 20) and normal controls (n = 21). In the temporal lobe area a significant (p < 0.05) diagnosis by side interaction was present, the area being less on the left than on the right side in patients with schizophrenia in contrast to findings in the two other groups. Lateral ventricular and temporal horn area did not distinguish the groups as a whole. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
1
6

Year Published

1989
1989
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(76 citation statements)
references
References 16 publications
8
61
1
6
Order By: Relevance
“…Magnetic resonance imaging (MRI) studies have consistently reported temporal lobe abnormalities in schizophrenia (e.g., Johnstone et al, 1989;Bogerts et al, 1990;Becker et al, 1996; see also reviews by Shenton et al, 1997Shenton et al, , 2001aPearlson, 1997;McCarley et al, 1999). Of particular note are MRI findings of Barta et al (1990) of an association between auditory hallucinations with anteriorsuperior temporal gyrus (STG) and the findings of Shenton et al (1992) of an association between posterior STG and thought disorder, which have spurred even greater interest in this brain region.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) studies have consistently reported temporal lobe abnormalities in schizophrenia (e.g., Johnstone et al, 1989;Bogerts et al, 1990;Becker et al, 1996; see also reviews by Shenton et al, 1997Shenton et al, , 2001aPearlson, 1997;McCarley et al, 1999). Of particular note are MRI findings of Barta et al (1990) of an association between auditory hallucinations with anteriorsuperior temporal gyrus (STG) and the findings of Shenton et al (1992) of an association between posterior STG and thought disorder, which have spurred even greater interest in this brain region.…”
Section: Introductionmentioning
confidence: 99%
“…8,137,138 Abnormalities of laterality have also been revealed by brain imaging studies measuring subregional tissue volume, blood flow, and metabolism. [139][140][141][142] The hippocampus and other temporal lobe structures appear to be prominently affected. There is an unclear relationship between these structural abnormalities, and the behavioral asymmetries in schizophrenia which are purportedly manifested in motor, sensory, language and cognitive function.…”
Section: Anomalous Cerebral Lateralizationmentioning
confidence: 99%
“…Currently, the most robust MR findings include enlargement of the lateral ventricles, especially in the left temporal horn (e.g. Johnstone et al, 1989;Dauphinais et al, 1990), and medial temporal lobe reduction (e.g. Woods et al, 1996), which, we note are likely "importantly related to disturbances in associative links in memory" (see review in Squire and Zola-Morgan, 1991;Squire, 1992;Nestor et al, 1993;Shenton et al, 1997, p. 340).…”
Section: Discussionmentioning
confidence: 80%